2021
DOI: 10.1007/s10924-021-02210-6
|View full text |Cite
|
Sign up to set email alerts
|

Inulin–Niacin Conjugates: Preparation, Characterization, Kinetic and In Vitro Release Studies

Abstract: Niacin, an essential B-complex vitamin, used in the treatment of nonalcoholic fatty liver disease is the rst perceived lipid regulating medication, inhibits and reverses hepatic steatosis and in ammation in animals and liver cell cultures. Niacin shows bene cial effects on adiposity. Niacin plays an important role in DNA repair, electron transfer, one-carbon metabolism and fatty acid synthesis in cells. Natural polysaccharides with desirable chemical modi cations can be combined with vitamins for developing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These surface-functionalized CDs were shown to be physicochemically and photochemically stable. , CDs also showed high two-photon absorption renderings, allowing fluorescence imaging with both one- and two-photon excitations on the same system. , In this study, we reported inulin covalently linked CDs to reduce toxicity. Inulin is a biocompatible natural polysaccharide containing a fructose-type structure that has uses in the pharmaceutical and culinary industries . Also, inulin is freely accessible and cannot be destroyed by enzymes in the human body because it is exogenous to the human body and can be easily changed, increasing its usefulness .…”
Section: Introductionmentioning
confidence: 99%
“…These surface-functionalized CDs were shown to be physicochemically and photochemically stable. , CDs also showed high two-photon absorption renderings, allowing fluorescence imaging with both one- and two-photon excitations on the same system. , In this study, we reported inulin covalently linked CDs to reduce toxicity. Inulin is a biocompatible natural polysaccharide containing a fructose-type structure that has uses in the pharmaceutical and culinary industries . Also, inulin is freely accessible and cannot be destroyed by enzymes in the human body because it is exogenous to the human body and can be easily changed, increasing its usefulness .…”
Section: Introductionmentioning
confidence: 99%